Trunfos de uma geografia activa: desenvolvimento local, ambiente, ordenamento e tecnologia - Lúcio Cunha (Documentos, 2011)
Geography, a science of synthesis and integration of social and natural phenomena, has become increasingly important as an applied discipline. This is due not only to the understanding that it provides of the world on different scales, but also to its intervention on the economic, social and cultural levels, helping to promote active citizenship and contributing to sustainable development and quality of life.ALT_QUEBRA_LINHAStarting from this premise and from the need to bring together Portuguese geographers for the debate on how geography can study space, understand places, organize territories, feel people, promote development, create options for political decision-making and even decide upon and promote development around theoretical and methodological questions of the application of geographic studies, the Portuguese Geographers' Association organized, in collaboration with the Department of Geography at the University of Coimbra and CEGOT, the 7th Conference of Portuguese Geography, ("Advantages of active geography: local development, environment, planning and technology". The main results are presented here in the form of this book.